Effects of Dietary Soybean Meal Concentration with Dietary Crude Protein Fixed at 12% on Growth and Carcass Performance of Finishing Pigs from 250 to 300 lb - J. Soto; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 280 pigs (DNA 600 × 241, initially 251.8 lb) were used in a 23-d trial to determine the effects of dietary soybean meal (SBM) concentration with dietary crude protein, fixed at 12%, on growth performance of finishing pigs from 250 to 300 lb. Pens of 7 or 8 pigs were allotted by BW and randomly assigned to 1 of 6 dietary treatments with 6 replications per treatment. Treatments consisting of 5 levels of SBM (10.6, 7.7, 4.9, 2.7, and 0%) with 12% CP and a negative control treatment with 4.0% SBM and 10% CP. Corn gluten meal was increased as SBM decreased to maintain the 12% CP. At d 23, pigs were transported to a packing plant for processing and carcass data collection. For overall growth performance, decreasing SBM marginally decreased (linear, P<0.10) ADG. Decreasing SBM increased (linear, P<0.05) ADFI with the highest intake in pigs that were fed 2.7% SBM. The high ADFI worsened (linear, P<0.05) F/G and caloric efficiency, resulting in pigs fed 2.7% SBM having the poorest caloric efficiency. Feed intake was lowered (P<0.05) in pigs fed the diet with 12% CP and 10.6% SBM compared with pigs fed the diet with 10% CP and 4.0% SBM, resulting in a marginal improvement (P<0.10) in F/G and caloric efficiency for pigs fed the 12% CP and 10.6% SBM diet. For carcass characteristics, decreasing SBM decreased (linear, P<0.05) carcass ADG and worsened (linear, P<0.05) carcass feed efficiency and caloric efficiency. Pigs fed the diet with 12% CP and 10.6% SBM had improved (P<0.05) F/G and marginally improved (P<0.10) carcass caloric efficiency compared with pigs fed the diet with 10% CP and 4.0% SBM. In conclusion, regardless of the 12% CP level, reducing the concentration of SBM worsened ADG, F/G, caloric efficiency, carcass ADG, and carcass feed efficiency, and caloric efficiency. In addition, pigs fed the 12% CP and 10.6% SBM had improved F/G, caloric efficiency, carcass feed efficiency, and carcass caloric efficiency, compared with pigs fed the negative control diet with 10% CP.
Keywords: soybean meal; crude protein; finishing pigs